Navigating the Rise of Cannabidiol: Trends, Challenges, and Future Directions - Erik Johansson; Joakim Quennerstedt; Anneli Eva Langer; Stenberg Kullander (Journal of Advances in Medicine and Pharmaceutical Sciences, 2025)
The use of cannabidiol (CBD) as an alternative treatment for chronic pain and anxiety is experiencing a rapid rise in Sweden. This study explores current trends, patient and healthcare provider perceptions, regulatory challenges, and barriers to broader CBD adoption. Employing a mixed-methods design, quantitative surveys and qualitative interviews are conducted with CBD users and healthcare professionals across various regions in Sweden. Findings indicate that CBD usage is highest in urban areas, driven by greater accessibility and wellness culture. Patients report moderate to high satisfaction, particularly for chronic pain management, although self-medication practices and lack of professional guidance are common. Healthcare providers exhibit cautious optimism, citing the need for further clinical validation and regulatory clarity. Safety concerns such as inaccurate product labeling and financial barriers, including the absence of insurance coverage for CBD, emerge as significant obstacles. Demographic analysis reveals differing usage patterns based on age but minimal gender differences. The study highlights the urgent need for standardized dosing guidelines, rigorous randomized controlled trials (RCTs), and stronger regulatory frameworks to ensure quality and equity in CBD treatment. Sweden’s progressive healthcare landscape positions it to play a leading role in global efforts to integrate CBD responsibly into mainstream medicine. Future research must bridge clinical, regulatory, and economic gaps to support CBD’s evolution as a legitimate therapeutic option worldwide.